Bacterial community structure and function distinguish gut sites in captive red‐shanked doucs (Pygathrix nemaeus). Issue 10 (18th April 2019) - Clayton, Jonathan B.; Shields‐Cutler, Robin R.; Hoops, Susan L.; Al‐Ghalith, Gabriel A.; Sha, John C. M.; Johnson, Timothy J.; Knights, Dan
Abstract : Abstract: The mammalian order primates contains wide species diversity. Members of the subfamily Colobinae are unique amongst extant primates in that their gastrointestinal systems more closely resemble those of ruminants than other members of the primate order. In the growing literature surrounding nonhuman primate microbiomes, analysis of microbial communities has been limited to the hindgut, since few studies have captured data on other gut sites, including the foregut of colobine primates. In this study, we used the red‐shanked douc ( Pygathrix nemaeus ) as a model for colobine primates to study the relationship between gastrointestinal bacterial community structure and gut site within and between subjects. We analyzed fecal and pregastric stomach content samples, representative of the hindgut and foregut respectively, using 16S recombinant DNA (rDNA) sequencing and identified microbiota using closed‐reference operational taxonomic unit (OTU) picking against the GreenGenes database. Our results show divergent bacterial communities clearly distinguish the foregut and hindgut microbiomes. We found higher bacterial biodiversity and a higher Firmicutes:Bacteroides ratio in the hindgut as opposed to the foregut. These gut sites showed strong associations with bacterial function. Specifically, energy metabolism was upregulated in the hindgut, whereas detoxification was increased in the foregut. Our results suggest a red‐shanked douc's foregut microbiome is no more concordant with its own hindgut than it is with any other red‐shanked douc's hindgut microbiome, thus reinforcing the notion that the bacterial communities of the foregut and hindgut are distinctly unique. Open Practices: This article has been awarded Open Materials and Open Data badges. All materials and data are publicly accessible via the IRIS Repository at https://www.iris-database.org/iris/app/home/detail?id=york:934328 . Learn more about the Open Practices badges from the Center for Open Science: https://osf.io/tvyxz/wiki . Abstract :